Malaysian judicial appointments commission and independent judiciary: a change we believe in? - Shuaib, Farid Sufian (2009)
Much works has been done to show the importance of judiciary in the healthy functioning of a state, particularly one that believe in rights and duties of the governed and the government. The extensive power hold by the combined might of the executive and the legislature in a Westminster style of government as adopted in Malaysia requires not less than a strong and independent judiciary. If the judiciary also falls to the lure of power and greed, all are doom. Judiciary also hold great influence in determining liberty of persons. When more cases relating to fundamental liberties were brought to the courts, judges position gain more importance. Disputes between individuals, between the have and the have not, the weak and the powerful, and between the governments at various levels requires judges of the highest calibre and integrity. To ensure we have an independent judiciary to decide such cases, it has to start with correct appointment process.